The role of institutional quality in the relationship between financial development and economic growth: Emerging markets and middle-income economies - Yuksel Bayraktar; Ayfer Ozyilmaz; Metin Toprak; Mehmet Firat Olgun; Esme Isik (Borsa Istanbul Review, 2023)
In this study, the relationship between economic growth and financial development was analyzed for emerging markets and middle-income economies. The effect of financial development on growth, whether there is institutional quality or not, has also been investigated. In addition, which financial development indicator is more effective for growth has been examined. Six institutional quality indicators and seven financial development indicators were used. According to the Dumitrescu–Hurlin causality test results, there is a causality relationship between all financial development indicators and growth. According to the estimation results, financial development indicators have a positive effect on growth in the presence of institutional quality. However, if institutionalization is not included in the model, the effect of financial development indicators on economic growth is statistically insignificant.